Independent Learning: Forming The Pancasila Learner Through Historical Learning In Senior High School - Anju Nofarof Hasudungan; Nur Fatah Abidin (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
In the midst of the industrial revolution 4.0 and the rise of identity politics and populism. Therefore, a policy is needed that brings back Pancasila as the identity of the nation. Through the concept of Free Learning education, the Minister of Education and Culture (Mendikbud) of the Republic of Indonesia strives to generate profiles of Pancasila students. The Ministry of Education provides six indicators of pancasila student profile. Namely, noble morality, creativity, mutual assistance, global diversity, critical reasoning, and self-reliance. Historical subjects are considered as subjects capable of shaping the profile of Pancasila students. Especially in high school, historical subjects have a relatively large share in terms of time allocation. Besides, the relevance between Pancasila and history lessons gives space for teachers to explore and instil Pancasila values in students. The purpose of this research is to describe the formation of Pancasila Student Profile through historical learning. This research uses qualitative research methods of descriptive analysis. Data collection methods use literature and document studies. It is hoped that through historical learning both through the content of the content and the learning process and its relevance to Pancasila, the establishment of Pancasila Student Profile becomes an inevitable.